The effect of using the cognitive trips strategy through The Web Quest toward tenth-grade students Motivation in social studies in the Sultanate of Oman - Al-Toubi, Khalid Nasser Abdullah; Mai, Mohammed Youssef (Journal of Curriculum and Teaching Methodology, 2023)
This study aims to recognize the effects in using the cognitive trip via the web quest on the fields of motivation with grade ten students within the course of social studies in the Sultanate of Oman. However, to achieve the research goals, the researcher has used the quasi-experimental approach for a sample consist of 120 students, to be specific 60 male students from the primary school of Abu Zaid Al-Ryami, and 60 female students from the Al Qalah primary school, within the course of social studies in the unit of geography. Moreover, the sample was divided into two experimental groups of (60) students cognitive trips strategy via the web, and the control group consisted of (60) students studying in the casual way. The researcher has designed an educational material on a website, which is the basis of the application depending on the teacher's guide prepared by the researcher. The researcher used a Motivation scale to collect data. The (T) test was used to check the equivalent of the experimental and control groups before using the cognitive trips strategy through the web quest. The results of this research revealed that there are statistically significant differences between the control and experimental groups in the motivation scale in favor of the experimental group. The results indicated also that there is non- significant, differences between males and females in experimental group. The results showed also that there is significant effect of the interaction between group and gender on motivation of the grade ten students. The study recommended the importance of employing the strategy of cognitive trip via the web in teaching social studies in the geography unit, qualifying and training teachers to use it, and conducting more studies on the use of this strategy in other research variables.
Keywords: web quest; cooperative groups; scholastic achievement